Evaluating municipal solid waste management using life cycle analysis: a case study - Oztas, Serpil; Erses Yay, Suna Aliye; Bektas, Nihal (Taylor & Francis Inc, 2022)
Every municipality in Turkiye regulates and implements its own specific waste management plan in line with the laws and regulations determined by the Ministry of Environment and Urbanization. umraniye District Municipality is selected as a case in the region for this study on solid waste management. Considering the solid waste characteristics in the district, seven different scenarios were defined for a systematic evaluation of solid waste management including the current method. The software program SimaPro 9.0 was used in the life cycle assessment, for the impact of the proposed scenarios on the environment and human health. 1 ton has been determined as a functional unit in the system. The scenarios were designed according to the waste characteristics of the region. Data obtained from the field and data obtained from similar literature studies have been utilized. The scenarios were compared through the methods EF (Environmental Footprint) Method 1.0 and ReCiPe 2016 Endpoint H. The evaluations were done for midpoint categories such as climate change, ozone layer depletion and eutrophication. The results from the LCA studies indicate that S-0 has the most negative impact in all the categories that were analyzed, except ozone depletion and resources-energy category, because of generating LFG (Landfilling Gas). The program outputs that seen from the program outputs, the S-0 CO2 emission value is 1.85E +08 kg CO2 eq with a high emission value. Similarly, S-0 is the scenario that has the most negative impact on human health, with 0.00071 kg of cadmium load due to the high rate of landfilling. Besides, S-4 has the lowest ozone depletion effect with its -0.00913 kg CFC11eq value. Finally, it is understood from the study, that an integrated waste management system (S-6) including incineration, composting, recycling, and a small percentage of landfilling- has lower environmental impact than current practice and other scenarios according to Climate change, photochemical ozone formation, non-cancer human-health effects, respectively, with 1.33E8 kg CO2 eq, 1.18E6 kg NMVOC eq and 4.02 CTUh values. Therefore, choosing the most sustainable waste management option can help to create a world-wide model environment friendly and smart city managements.
Keywords: Municipal solid waste management (MSWM); Life cycle assessment (LCA); SimaPro 9; 0; Environmental impacts